2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34796
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student Accessibility, Equity, Course Performance, and Lab Skills: How Introduction of ClassTranscribe is Changing Engineering Education at the University of Illinois

Abstract: His interests include (but are not limited to) joyful teaching, empirically-sound educational research, campus and online courses, computer science, unlocking the potential of underrepresented minorities, improving accessibility and creating novel methods that encourage new learning opportunities and foster vibrant learning communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…There exist educational systems, such as ClassTranscribe (Ren et al, 2015) and ICS Videos (Deshpande et al, 2014), that can generate captions for lecture videos in a collaborative fashion with learners. Previous studies (Deshpande et al, 2014;Angrave et al, 2020a;Cross et al, 2014) have shown that such tools are effective and efficient for captioning lecture videos and have considerable value in educational practice (Angrave et al, 2020a(Angrave et al, , 2020bAmos et al, 2021;Zhang etal, 2021;Zhang, 2021). Previous research has also shown that involving learners in fixing captions in foreign language educational videos does not impair learning and also helps reduce errors in the captions (Culbertson et al, 2017).…”
Section: Collaborative Video Captioningmentioning
confidence: 99%
“…There exist educational systems, such as ClassTranscribe (Ren et al, 2015) and ICS Videos (Deshpande et al, 2014), that can generate captions for lecture videos in a collaborative fashion with learners. Previous studies (Deshpande et al, 2014;Angrave et al, 2020a;Cross et al, 2014) have shown that such tools are effective and efficient for captioning lecture videos and have considerable value in educational practice (Angrave et al, 2020a(Angrave et al, , 2020bAmos et al, 2021;Zhang etal, 2021;Zhang, 2021). Previous research has also shown that involving learners in fixing captions in foreign language educational videos does not impair learning and also helps reduce errors in the captions (Culbertson et al, 2017).…”
Section: Collaborative Video Captioningmentioning
confidence: 99%
“…Conversely, the introduction of searchable video lectures in an undergraduate-level system programming course which complemented the equivalent online book content caused an increase in course performance for all students [7]. Similarly in an introduction to electronics class, searchable translated class videos led to improved course scores [8].…”
Section: Universal Design For Learningmentioning
confidence: 99%
“…The components of the MUSIC model have been used for the past decade in multiple contexts to identify factors that motivate students [9,10]. Highlights of peer-reviewed course performance models and student feedback showed that searching as a new modality is correlated with positive perceptions and improved student performance [7,8].…”
Section: Universal Design For Learningmentioning
confidence: 99%
“…ClassTranscribe is a web-based learning system and video lecture platform that has more than 13,000 users. Some of its features have been previously presented at ASEE [4,23,15]. Its adoption has led to measurable and statistically significant improvements in learning outcomes [5] and large scale studies of the importance of UDL for engineering students with and without disabilities, for example, [2,14].…”
Section: Classtranscribementioning
confidence: 99%